2011
DOI: 10.1007/s10499-011-9453-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous dietary enzyme on growth, body composition, and fatty acid profiles of cultured great sturgeon Huso huso fingerlings

Abstract: The effects of enzyme supplementation on growth, body proximate, and fatty acid composition of great sturgeon Huso huso fingerlings were investigated. Multienzyme (Kemin Ò ) was added to diet in different concentrations (0, 250, 500, 750, and 1,000 mg/ kg). Fingerlings were randomly stocked in tanks and fed with the experimental diets three times a day at 5-10% body weight for 46 days. Fingerlings fed diets containing 250 mg/kg exogenous enzyme exhibited higher weight gain and specific growth rate. This level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
34
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 8 publications
10
34
0
2
Order By: Relevance
“…Zhou et al (2013) also found that cellulase supplemented duckweed based diet promoted the growth of grass carp. Present result is also supported by finding of Ai et al (2007), Yildrim and Turan (2010), Ghomi et al (2012) and Zamini et al (2014), who also reported positive effect of various commercial multi-enzyme complex (phytase, xylanase, β-glucanase, amylase, cellulase and pectinase) on the growth performance and feed efficiency of Lateolabrax japonicas, Clarias gariepinus, Huso huso and Salmo trutta, respectively. Improved growth performance and nutrient utilization of Labeo rohita fed DORB based diet supplemented with exogenous enzymes may be contributed to the elimination of anti-nutritional factors and improving the utilization of dietary energy and amino acid.…”
Section: Discussionsupporting
confidence: 85%
“…Zhou et al (2013) also found that cellulase supplemented duckweed based diet promoted the growth of grass carp. Present result is also supported by finding of Ai et al (2007), Yildrim and Turan (2010), Ghomi et al (2012) and Zamini et al (2014), who also reported positive effect of various commercial multi-enzyme complex (phytase, xylanase, β-glucanase, amylase, cellulase and pectinase) on the growth performance and feed efficiency of Lateolabrax japonicas, Clarias gariepinus, Huso huso and Salmo trutta, respectively. Improved growth performance and nutrient utilization of Labeo rohita fed DORB based diet supplemented with exogenous enzymes may be contributed to the elimination of anti-nutritional factors and improving the utilization of dietary energy and amino acid.…”
Section: Discussionsupporting
confidence: 85%
“…More recently, Yildirim and Turan (2010), Ghomi et al (2012), and Zamini et al (2014) found a positive effect of various commercial multi-enzyme complexes (phytase, xylanase, β-glucanase, β-amylase, cellulase and pectinase) on the growth performance and feed efficiency of African catfish (Clarias gariepinus), great sturgeon (Huso huso) and Caspian salmon (Salmo trutta), respectively. However, no specified plant-based feedstuffs were used in any of these studies.…”
Section: Soybean Mealmentioning
confidence: 99%
“…However, no specified plant-based feedstuffs were used in any of these studies. Nonetheless, Ghomi et al (2012) reported that sturgeon fingerlings fed with 500 mg kg −1 enzyme mix in the diet had higher contents of n−3 essential fatty acids and lower n−6/n−3 fatty acid ratio in the muscle. Kiarie et al (2009) indicated that in piglets fed diets containing carbohydrases, the contents of essential polyunsaturated fatty acids increased compared with animals fed diets without enzymes.…”
Section: Soybean Mealmentioning
confidence: 99%
“…There is growing interest to culture beluga sturgeon in Iran due to its large size, fast growth rate and tasty flesh (Ghomi et al 2011). The aim of the present study was to evaluate the effect of soybean meal and multienzyme supplementation on intestinal histopathology of beluga sturgeon (Huso huso) and whether enzyme supplementation can reduce the negative impact of SBM diet on histopathological changes of beluga intestine.…”
Section: Introductionmentioning
confidence: 97%